Ambience and productive performance of arugula cultivated in different spacing - Gonçalves-Trevisoli, Edilaine Della Valentina; Mendonça, Heloísa Ferro Constâncio; Dildey, Omari Dangelo Forlin; Dartora, Janaína; Rissato, Bruna Broti; Coltro-Roncato, Sidiane; Klosowski, Élcio Silvério; Tsutsumi, Cláudio Yuji; Echer, Marcia de Morais (Scientia Agraria Paranaensis, 2017)
<span style="font-size: 10pt; font-family: ’Helvetica’,sans-serif; mso-fareast-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-font-family: ’Times New Roman’;" lang="EN-US">The objective of this work was to evaluate the effect of environment on the productive performance of arugula in different row spacings and plant spacing. The experiment was conducted in the spring and summer 2011 and in the autumn and winter 2012. The experiment design was a randomized complete block design with four replications in a 3 x 2 factorial design. The first factor consisted to the row spacings (0.20; 0.25 and 0.30 m) and the second to the plant spacings (0.05 and 0.10 m). The plant height and diameter, leaf number, leaf area and total leaf fresh matter and productivity were evaluated. The data were subjected to variance analysis and the averages were compared by Tukey test (p < 0.05). In the spring and in the plant spacing of 0.05 m were verified higher plants. For diameter and leaf area there was only seasonal effect whose averages were higher in winter and spring. The interaction between growing season and spacing of plants showed a highest leaves number and the total leaf fresh matter occur in the spring and winter in plant spacing of 0.10 m. Was obtained in the spring with row spacing of 0.20 m. The best productive performance was obtained for plants in a plant spacing of 0.05 m.